2021
DOI: 10.1186/s13018-021-02720-y
|View full text |Cite
|
Sign up to set email alerts
|

Adipogenic differentiation was inhibited by downregulation of PPARγ signaling pathway in aging tendon stem/progenitor cells

Abstract: Background Tendon stem/progenitor cells (TSPCs) play a vital role in tendon repair and regeneration. Previously we found more adipocytes accumulated in the patellar tendon injury sites in aging rats compared with the young ones, of which the mechanism is still unknown. Here, we want to identify whether erroneous differentiation of TSPCs by aging accounts for the adipocyte accumulation. Methods TSPCs from young and aging rats were isolated and propa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 28 publications
(31 reference statements)
0
5
0
Order By: Relevance
“…Long noncoding RNA MEG3 inhibits the osteogenic differentiation potential of TDSCs through the miR-129-5p/transcription factor 4 (TCF4)/β-Catenin axis, thus reducing ectopic ossification caused by trauma in tendon tissue ( Liu et al, 2023b ). Vascular endothelial growth factor (VEGF) and PPAR gamma can also suppress adipogenic differentiation of TDSCs, presenting them as promising therapeutic targets for tendon degeneration ( Lai et al, 2021 ; Lai et al, 2022 ). The recruitment and accumulation of endogenous TDSCs at the site of tendon injury initiate their participation in the repair process.…”
Section: Discussionmentioning
confidence: 99%
“…Long noncoding RNA MEG3 inhibits the osteogenic differentiation potential of TDSCs through the miR-129-5p/transcription factor 4 (TCF4)/β-Catenin axis, thus reducing ectopic ossification caused by trauma in tendon tissue ( Liu et al, 2023b ). Vascular endothelial growth factor (VEGF) and PPAR gamma can also suppress adipogenic differentiation of TDSCs, presenting them as promising therapeutic targets for tendon degeneration ( Lai et al, 2021 ; Lai et al, 2022 ). The recruitment and accumulation of endogenous TDSCs at the site of tendon injury initiate their participation in the repair process.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to this, A-TSPCs express higher levels of CD44 compared to Y-TSPCs, suggesting a poorer healing capacity of the injured tissue. By contrast, Lai et al [ 105 ] showed that the patellar tendon adipose accumulation in aged rats was not due to A-TSPC, but due to inhibition of PPAR γ signaling pathway by aging, thereby preventing adipogenesis in TSPCs. To verify the adipogenic capacity of senescent TSPCs, they were tested in vitro for oil red O staining, and the number of fat droplets in senescent TSPCs was found to be significantly reduced.…”
Section: Tendon Stem/progenitor Cells May Account For the Failure Of ...mentioning
confidence: 97%
“…The cAMP/PKA pathway has been involved in the regulation of adipogenic differentiation of tendon stem cells (TSCs) by IGF-1 and BMP-2 (Liu et al 2014). TSCs are derived from tendon tissues and are the endogenous cell source for tenocyte turnover and tendon functional maintenance, playing a vital role in tendon repair and regeneration (Shi et al 2017;Lai et al 2021). We therefore hypothesized that GATA6 could affect the fatty infiltration and bone-tendon healing after RCT via regulation of the Caveolin-1/cAMP/ PKA axis.…”
Section: Introductionmentioning
confidence: 99%